The Use of GIS for Supporting the Experimental Representation of the Selected Supply Network in Pafos Municipality — 'The Hydrogis Lab' - Themistocleous, Kyriacos; Evlogimenos, Ploutarchos; Agapiou, Athos; Hadjimitsis, Diofantos G. (My University, 2014)
The HydroGIS Lab project (http://cyprusremotesensing.com/hydrogis/) aims to satisfy the dire need for authorities to solve the extremely serious problem of water supply as a result of continued water shortage. The chronic problems of water losses in the water supply network pipes, the uncontrolled and non-optimum operation of pumping stations, the incorrect design of the networks because of various interventions such as town planning and erroneous mapping of existing networks, are some of the most important problems which need to be resolved in order to optimize the performance of the networks and, consequent‐ ly, save water and energy. The innovative aspect of the Project is that state-of-the-art technologies are combined for the mapping of water networks through the Global Position‐ ing System (GPS), Radar Scanners and Satellite Remote Sensing (SRS). The data is entered into a Geographic Information System (GIS), with the aim of developing a digital imprint and the mapping of the network. The study of an existing selected water supply network and the collection of the necessary information by the Cyprus University of Technology and the Water Development for the network and its systems will lead to an imaging of water pipes and their design using a radar scanner and special software and GIS. Satellite im‐ ages, which have been transformed into the local reference system using specialized software, will be coupled with the digital imaging of the existing maps. This information will then be organized in such a way allowing the development of maps and their analysis at different levels (e.g. water supply network, buildings, water supply elements, geographic informa‐ tion, features of the network’s systems, etc.).
Keywords: Water supply; Water shortage; Pumping stations; Global Position‐ ing System (GPS); Geographic Information System (GIS)